Combined Effect of Sex and Age in Response to Antiretroviral Therapy in HIV-Infected Patients. Issue 1 (January 2017) - ,; Blanco, Jose Ramón; Jarrin, Inma; Pérez-Elías, Maria Jesús; Gutiérrez, Félix; Hernández-Quero, José; Portilla, Joaquín; Dalmau, David; Moreno, Santiago; Hernando, Victoria
Background: Gender-specific data on the management of HIV infection are scarce. Further, an increase in the proportion of new HIV diagnoses in older persons has been observed. Using data from the CoRIS cohort, we compared immunovirological responses and survival in HIV-infected men and women who started their first combination anti-retroviral therapy (cART) when aged </≥50 years. Methods: We used multivariable logistic, linear and Cox regression, adjusting for potential confounders and including an interaction between age and sex, to assess differences in immunovirological responses and mortality, respectively. Results: At 96 weeks, among subjects <50 years, women were less likely than men to achieve virological response (VR; adjusted OR [aOR] 0.77, 95% CI 0.60, 0.99) and among women, older individuals were more likely to achieve VR than the younger ones (aOR 1.96; 95% CI 1.15, 3.34). Initiating cART at ≥50 years was associated with lower increases in CD4 + T-cell count both in men (-65.8; 95% CI -91.3, -40.3) and women (-37.7; 95% CI -79.7, 4.4) and women showed higher increases than men in both subjects aged <50 (21.8; 95% CI -1.9, 45.5) and ≥50 years at cART initiation (49.9; 95% CI 19.9, 79.9). A higher risk of death in men ≥50 was observed (adjusted hazard ratio [aHR] 2.69; 95% CI 1.73, 4.21), but not in women (aHR 1.49; 95% CI 0.70, 1.14). Women experienced lower mortality than men <50 (0.66; 95% CI 0.41, 1.07) and in those ≥50 (0.37; 95% CI 0.14, 0.93). Conclusions: Sex and age at cART initiation have a noticeable association with both virological and immunological responses and mortality. Age ≥50 is associated with poorer immunological response and higher mortality but this effect is less pronounced in women than in men.